Development of a Construct 2-Based Educational Game for Flag Recognition Through Word Puzzles in Indonesian Primary Schools - Gunawan, Syahrul; Munawir, Ahmad; Amaldi, Wahyu (JINAV: Journal of Information and Visualization, 2025)
This study aims to develop an interactive educational game titled Flag Letter Puzzle using Construct 2, intended to enhance the learning experience of third-grade students at SDN Patra Manggala 2, Tangerang Regency. The game introduces students to country flags through an engaging word puzzle format that supports both cognitive development and national awareness. The research employed the Research and Development (R&D) approach using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. During the analysis stage, observations and interviews were conducted to identify student needs and the relevance of educational media in the classroom. The design phase involved creating the storyboard, interface, and gameplay structure tailored for young learners. The game was developed using Construct 2, enabling integration of visuals, sound, and interactivity. Implementation involved a trial run with 20 students, and the final evaluation was conducted using Black Box Testing and user feedback. The results showed that all game features functioned properly according to expectations. Students responded positively, displaying high levels of engagement and enjoyment during the learning activities. The intuitive interface and interactive gameplay facilitated independent learning, improved memory retention, and promoted curiosity. The game also aligns well with the 2013 Indonesian curriculum (Kurikulum 2013), particularly in Social Studies and Civics, which emphasize knowledge of national symbols and neighboring countries. This research concludes that the Flag Letter Puzzle game is both technically feasible and pedagogically effective. It provides a valuable alternative to conventional learning methods by integrating game-based learning into the classroom. The application not only serves as a tool for reinforcing knowledge of country flags but also fosters active learning and digital literacy among elementary school students. The game is recommended for use in similar educational settings to support curriculum delivery and improve learning outcomes through interactive media.